2011
DOI: 10.4314/ajpherd.v17i3.68079
|View full text |Cite
|
Sign up to set email alerts
|

Sports for learners with physical disabilities in ordinary public primary schools in the Western Cape, South Africa

Abstract: In the Western Cape, learners with physical disabilities are accepted into ordinary schools (a school that is not a special school) as a part of the inclusive education initiative. This article reports on a survey designed to determine the types of sports that are available for learners with physical disabilities in ordinary public primary schools and the factors influencing their participation in sport. The study sample included 31 learners with physical disabilities (learners with movement or mobility diffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In all four school contexts the inclusion of PE in the curriculum to enhance and improve performance in school sport and ultimately sport as a whole is supported for reasons that include the following: helps with cognitive development and selfconfidence; helps learners to get fit and healthy; is considered to be very important in helping learners to stay away from smoking, crime, alcohol, and drugs, including glue and whoonga (street drug), that is rife in the township in particular; and provides an opportunity for academically weak learners to possibly express themselves on the field. Educators, learners, and other role-players, such as subject advisors, have reported that they value both school sports and PE for their contribution to learners' health in the studies of Nongogo et al [66], Hollander [106] and Stroebel, Hay and Bloemhoff [107], while Wegner and Struthers [108], as well as Moll and Bester [109] more specifically to learners with disabilities, asserted that it provides social support and is seen as a driver of social inclusion. In their study on the effect of participation in competitive sports on school connectedness of secondary school students, Kamau, Rintaugu, Muniu, and Amusa [110] concede that school type and school status, and lack of resources had a significant impact on participation in sport.…”
Section: Discussionmentioning
confidence: 99%
“…In all four school contexts the inclusion of PE in the curriculum to enhance and improve performance in school sport and ultimately sport as a whole is supported for reasons that include the following: helps with cognitive development and selfconfidence; helps learners to get fit and healthy; is considered to be very important in helping learners to stay away from smoking, crime, alcohol, and drugs, including glue and whoonga (street drug), that is rife in the township in particular; and provides an opportunity for academically weak learners to possibly express themselves on the field. Educators, learners, and other role-players, such as subject advisors, have reported that they value both school sports and PE for their contribution to learners' health in the studies of Nongogo et al [66], Hollander [106] and Stroebel, Hay and Bloemhoff [107], while Wegner and Struthers [108], as well as Moll and Bester [109] more specifically to learners with disabilities, asserted that it provides social support and is seen as a driver of social inclusion. In their study on the effect of participation in competitive sports on school connectedness of secondary school students, Kamau, Rintaugu, Muniu, and Amusa [110] concede that school type and school status, and lack of resources had a significant impact on participation in sport.…”
Section: Discussionmentioning
confidence: 99%
“…In all four school contexts the inclusion of PE in the curriculum to enhance and improve performance in school sport and ultimately sport as a whole is supported for reasons that include the following: helps with cognitive development and selfconfidence; helps learners to get fit and healthy; is considered to be very important in helping learners to stay away from smoking, crime, alcohol, and drugs, including glue and whoonga (street drug), that is rife in the township in particular; and provides an opportunity for academically weak learners to possibly express themselves on the field. Educators, learners, and other role-players, such as subject advisors, have reported that they value both school sports and PE for their contribution to learners' health in the studies of Nongogo et al [66], Hollander [106] and Stroebel, Hay and Bloemhoff [107], while Wegner and Struthers [108], as well as Moll and Bester [109] more specifically to learners with disabilities, asserted that it provides social support and is seen as a driver of social inclusion. In their study on the effect of participation in competitive sports on school connectedness of secondary school students, Kamau, Rintaugu, Muniu, and Amusa [110] concede that school type and school status, and lack of resources had a significant impact on participation in sport.…”
Section: Discussionmentioning
confidence: 99%